Evaluasi Pengendalian Intern pada Penerapan Tapping Box untuk Mencegah Kecurangan dalam Pelaporan Pajak dan Mengefektifkan Penerimaan Pajak Daerah - Anissa Putri Rahmawati; Putra, Sugih Sutrisno (Indonesian Accounting Research Journal, 2023)
This study aims to evaluate the extent to which the effectiveness of internal control in the application of tapping boxes at the Regional Revenue Agency of West Bandung Regency, considering that the number of applications has not been maximized, namely only 25 out of 100 tools provided. Research data which is subject data with primary data sources were collected through interviews with the Regional Revenue Agency and questionnaires aimed at all registered taxpayers who have installed tapping box tools in West Bandung Regency. Data analysis was carried out on five sub-variables and 18 dimensions of internal control which were collected through a questionnaire. The research findings indicate that the internal control system for the application of tapping boxes is still inadequate. Based on these results, relevant government agencies need to improve the implementation of internal control on components with low scores, so that internal control can become more effective and tapping box implementation can be maximized. As for the taxpayer, it is hoped that they will be more coordinative with the government regarding the application of the tapping box tool at their place of business.